Unconventional green - Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
We analyze the effects of the PEPP (Pandemic Emergency Purchase Programme), the temporary quantitative easing implemented by the ECB immediately after the burst of the Covid-19 pandemic. We show that the differences in aim, size and flexibility with respect to the traditional Corporate Sector Purchase Programme (CSPP) were able to significantly involve, in addition to the directly targeted bonds, also the green bond segment. Via a standard difference-in-differences model we estimate that the yield on green bonds declined by more than 20 basis points after the PEPP. In order to take into account also the differences attributable to the eligibility to the programme, we employ a triple difference estimator. Bonds that at the same time were green and eligible benefitted of an additional premium of 39 basis points.
urn:nbn:de:hebis:30:3-691363
Keywords: G15; G32; E52; C21; 330; Green bonds; ECB; Corporate quantitative easing; triple difference estimator